Optimal Positioning for Advanced Raim. Issue 4 (10th December 2013) - Blanch, Juan; Walter, Todd; Enge, Per
ABSTRACT We present a method to improve the integrity error bound in Advanced RAIM by optimizing the position solution and the integrity allocation simultaneously. Since the reduction in the error bound is achieved by degrading the position accuracy under nominal conditions, the method takes into account the accuracy constraint in the optimization. Advanced RAIM may have to consider a larger number of satellites and increased probabilities of fault, so this method is designed to accept a wide variety of threat models (in particular multiple faults). The search of the optimal coefficients is cast as a convex optimization problem with constraints. The solution is obtained iteratively, and the convexity of the problem guarantees a very fast convergence. The algorithm is evaluated by comparing its performance with algorithms where the position solution is not optimized, and showing how it could help achieve worldwide coverage of vertical guidance (LPV‐200). Copyright © 2013 Institute of Navigation